Kurt Villads Jensen, Janus Møller-Jensen, Carsten Selch Jensen (eds.): Fighting for the Faith - The Many Crusades - Svenungsen, Pål Berg (Collegium Medievale, 2020)
The Crusades have been one of the most enduringly popular topics in medieval history among historians and a wider public alike, and crusade studies have reached an impressive critical mass over the last few decades. In the process, it has become one of the most cross-disciplinary fields within medieval history, encompassing a multitude of methodological and theoretical approaches. Fighting for the Faith - The Many Crusades aims to illustrate the variety in Crusade studies internationally. The initiative arose from general discussions about the Crusades among a group of Danish medievalist at the University of Southern Denmark in Odense, which led to further discussions at symposia and workshops around Europe and in the United States. In the "Introduction", Kurt Villads Jensen and Carsten Selch Jensen state that the aim of the book is to discuss "some of the fundamental questions of current Crusade studies, including the reasons for undertaking crusades, against whom to crusade, and the periods during which it was possible to go on crusades - as well as what happened subsequently" (p. 9). The anthology consists of fifteen articles that cover a broad range of themes related to the Crusades and aspects of crusading. The contributions are almost exclusively limited to textual analyses, with the exception of Theresa M. Vann's article on the role of images in the Hospitallers' early book production.